Quantitative HPLC analysis of sesquiterpene lactones and determination of chemotypes in Eremanthus seidelii MacLeish & Schumacher (Asteraceae) - Sakamoto, Humberto T.; Gobbo-Neto, Leonardo; Cavalheiro, Alberto José [UNESP]; Lopes, Norberto P.; Lopes, João L. C. (FapUNIFESP (SciELO), 2005)
Eremanthus seidelii MacLeish & Schumacher has a restricted occurrence to the Brazilian cerrado surrounding the Furnas (MG) reservoir, in environments that have been seriously damaged by human activity. The present phytochemical investigation reveals that the sesquiterpene lactones (SL) 4β,5-dihydro-2′,3′-dihydroxy-15-desoxy-goyazensolide (1) and 4β,5-dihydro-1′,2′-epoxy-eremantholide-C (2) are the major secondary metabolites in E. seidelii leaves, and an HPLC method was developed for their quantitative analysis. HPLC analysis showed no significant seasonal variation in the concentrations of both SL. No qualitative differences were found in the SL patterns of all individuals sampled. However, there is a different SL quantitative pattern among the plants analyzed, pointing to the existence of three quantitative chemotypes of this species, with differences possibly originating from the activity of the enzymes that cyclize the goyazensolide type SL (1) to a eremantholide type SL (2). ©2005 Sociedade Brasileira de Química.
Keywords: Chemotypes; Eremanthus seidelii; HPLC; Populational variation; Sesquiterpene lactones